Marketer as a Barbie Game Changer - Widyani, Donafeby; Joseph Chen (International Journal of Science, Technology & Management, 2021)
This paper addresses issues about how the Barbie doll can provide an unrealistic vision of how women should look and what marketers can do about it. Barbie is a well-known doll that has become a role model for girls. However, Barbie dolls have attracted much criticism. Studies found that Barbie shapes the body image of young girls and possibly creates body dissatisfaction and low self-esteem among girls. Body dissatisfaction can lead to eating disorders and low self-esteem can lead to depressive behavior. Answering that phenomenon, Barbie launched Barbie Fashionista that has a diverse body type. However, Girls still tend to choose thinner Barbie. Barbie’s marketer should encourage girls to play more with a more realistic body image Barbie such as curvy, tall, and petite, and encourage the children to feel good about their bodies.